Kajian Ekonomi Islam Tentang Kesesuaian SMS Berhadiah Dengan Prinsip-Prinsip Syariah - Irmawanti, Irmawanti; Mairiza, Diany (EL-EMIR Institute, 2024)
This research aims to examine the compliance of prize-winning SMS programs with Sharia principles from an Islamic legal perspective. In the rapidly developing digital era, promotions through prize-winning SMS have become a popular strategy among telecommunications companies. However, it is crucial to ensure that these programs do not violate Sharia principles such as the prohibitions against riba (usury), gharar (uncertainty), and maysir (gambling). This research uses a qualitative approach with a descriptive-analytical method, gathering primary data through in-depth interviews and questionnaires, as well as secondary data from relevant literature and documents.The results of the study indicate that although there are efforts by telecommunications companies to comply with Sharia principles, there are still some obstacles such as unclear costs and non-transparent drawing mechanisms. Muslim consumer perceptions of prize-winning SMS programs tend to be skeptical due to the lack of transparency and perceived unfairness in these programs. Fatwas and guidelines from scholars, as well as regulations in several Muslim countries, emphasize the importance of transparency, fairness, and the absence of maysir elements in any promotional program. This research suggests improving transparency, implementing Sharia audits, educating consumers, and developing stricter regulations to ensure the compliance of prize-winning SMS programs with Sharia principles. With these measures, prize-winning SMS programs can be conducted more fairly and transparently, enhancing the trust and satisfaction of Muslim consumers.